PENGARUH MODAL INTELEKTUAL DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bayu Trimurti Herlambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The objective of this research is to test the influence of intellectual capital and capital structure on the financial performance of banking companies listed in Indonesia Stock Exchange. The intellectual capital is measured with VAIC method which consists of a few components and they are VAHU, STVA and VACA. Moreover, the capital structure is measured with DER method and the financial performance is measured with ROE method. The quantitative method was applied in this research along with purposive sampling methodto collect the data in the form of secondary data which comprised of 111 banking companies in the period of 2013-2015. The results of this study indicate that the Intellectual Capital component, VAHU and VACA, has an impact on ROE, while STVA has no impact on ROE. DER variable gives a decrease in the form of ROE so that the hypothesis is rejected. This shows that the banking companies in Indonesia still rely on their physical assets which is measured by VACA and VAHU in creating added value for the companies that has an impact on the improvement of the financial performance of the companies. In addition, the banking companies management needs to manage their debt which is measured by DER as best as possible in order to prevent deteriorating performances of the companies. Thus the accepted hypotheses are VAHU and VACA, while the hypotheses rejected are STVA and DER.Keywords: Intellectual Capital, Structure Capital, Financial Performace, Banking Companies